Flexible Thermoelectric Devices Based on Indium Phosphide Nanowire Networks on Copper. Issue 1682 (29th August 2014) - Norris, Kate J.; Tuan, Brian; Coleman, Elane; Fryauf, David M.; Zhang, Junce; Tompa, Gary S.; Kobayashi, Nobuhiko P.
ABSTRACT: More than 50% of total input energy is wasted as heat in various industrial processes. If we could harness a small fraction of the waste heat while satisfying the economic demands of cost versus performance, then thermoelectric (TE) power generation could bring substantial positive impacts. To meet these demands single-crystal semiconductor nanowire networks have been investigated as a method to achieve advanced TE devices because of their predicted large reduction in thermal conductivity and increase in power factor. To further our goal of developing practical and economical TE devices, we designed and developed a material platform that combined a semiconductor nanowire network and a semiconductor thin film integrated directly on a mechanically flexible metallic substrate. We assessed the potential of this platform by using indium phosphide (InP) nanowire networks and a doped poly-silicon (poly-Si) thin film combined on copper sheets. InP nanowires were grown by metal organic chemical vapor deposition (MOCVD). In the nanowire network, InP nanowires were grown in three-dimensional networks in which electrical charges and heat travel under the influence of their characteristic scattering mechanisms over a distance much longer than the mean length of the constituent nanowires. Subsequently, plasma-assisted CVD was utilized to form a poly-Si thin film to prevent electrical shorting when an ohmic copper top contact was made. An additional facet to this design is the utilization of multiple materials to address the various temperature ranges at which each material is most efficient at heat-to-energy conversion. The utilization of multiple materials could enable the enhancement of total power generation for a given temperature gradient. We investigated the use of poly-Si thin films combined with InP nanowires to enhance TE properties. TE power production and challenges of a large area nanowire device on a flexible metallic substrate were presented.